An action research addressing delays in the preparation of the financial statements of Maxim Multi-Purpose Cooperative by creating an incentive plan to improve employee motivation - Salinas, Mikhail A. (Animo Repository, 2021)
This integrative action research is intended to address the persisting issue on MMPC’s financial reporting process as its audited financial statements are consistently delayed. As a result, the dividends being declared and distributed to members have been based only on the preliminary financial results, which are still subject to changes since the financial statements still have to be prepared and reviewed by its internal audit committee and external financial auditors. This issue brings a significant risk because if the audited financial statements eventually reflect a different net surplus than the preliminary numbers used to calculate dividends, then the dividends paid to members will turn out to be wrong. When this happens, the cooperative will have to announce the misstatement to members then subsequently recall its dividend declaration by either paying more or taking back a portion of the dividends that were already distributed to members. Operationally managing these adjustments can be very challenging, but more importantly, there is a severe risk of undermining members’ trust in the management of the cooperative when they hear problems related to financial inaccuracies.Since early 2019, I have been working closely with our cooperative staff and HR committee to develop the optimal action plan to address our issue holistically. We used Professor Ishikawa’s Fishbone Diagram in conjunction with “Five Whys analysis” and Systems Thinking to identify three root causes of our issue (i.e., inferior employee compensation package, lack of performance-based incentive, and absence of quarterly performance reviews) and how they were interconnected. Thus, in this project, we focused on creating a performance-based incentive plan to improve employee morale, motivation, and turnover.